Flavonoid Accumulation Varies in Medicago truncatula in Response to Mercury Stress - Alvarez-Rivera, Gerardo; Sanz, Aurora; Cifuentes, Alejandro; Ibánez, Elena; Paape, Timothy; Lucas, M. Mercedes; Pueyo, José J. (Frontiers in Plant Science, 2022)
Mercury (Hg) contamination is increasing worldwide in both wild ecosystems and agricultural soils due to natural processes and anthropogenic, but mostly to anthropic activities. The molecular mechanisms involved in Hg toxicity and tolerance in plants have been extensively studied; however, the role of flavonoids in response to Hg stress remains to be investigated. We conducted a metabolomic study to analyze the changes induced at the secondary metabolite level in one Hg-sensitive and three Hg-tolerant and one Hg-sensitive M. truncatula cultivars. A total of forty-six flavonoid compounds, classified into five different flavonoid families: anthocyanidins, flavones, isoflavones, pterocarpan flavonoids and flavanones, along with their respective glycoconjugate derivatives, were identified in leaf and root tissues. The synthesis of free isoflavones, followed by monoglycosylation and further malonylation was shown to be characteristic of root samples, whereas higher glycosylation, followed by further acylation with coumaric and ferulic acid was characteristic of leaf tissues. While minor changes were observed in leaves, significant quantitative changes could be observed in roots upon Hg treatment. Some flavonoids were strongly up-regulated in roots, including malonylglucosides of biochanin A, formononetin and medicarpin, and aglycones biochanin, daidzein and irisolidone. Hg tolerance appeared to be mainly associated to the accumulation of formononetin MalGlc, tricin GlcAGlcA and afrormosin Glc II in leaves, whereas aglycone accumulation was associated with tolerance to Hg stress in roots. This isThe results evidence thatthe alteration of the flavonoid metabolic profile and their glycosylation processes are quantitative responsesin response to Hg stress. However, notable differences existed between varieties, both in the basal metabolic profile and in the response to treatment with Hg. Overall, we observed an increase in flavonoid production in response to Hg stress, and Hg tolerance appeared to be associated to a characteristic glycosylation pattern in roots, associated with the accumulation of aglycones and monoglycosylated flavonoids. The findings are discussed in the context of the flavonoid biosynthetic pathway to provide a better understanding of the role of these secondary metabolites in the response and tolerance to Hg stress in M. truncatula.